Metonímia i metàfora des d'una perspectiva cognitiva - Hilferty, Joseph (Caplletra. Revista Internacional de Filologia, 1995)
The author presents some principles of Cognitive Linguistics useful in dealing with metonymy and metaphor as semantic resources in relation to idioms and proverbs. Beyond their interest for studies of Literature and Linguistics, these resources show how the human mind works.